2008
DOI: 10.1111/j.1365-2230.2008.02694.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus in children: review of 26 cases

Abstract: Lichen Planus (LP) is a common, very itchy papulosquamous disorder. Most reports of LP in children have come from the Indian subcontinent, suggesting that children of South Asian origin are more susceptible to developing LP. We conducted a retrospective, open, observational study of children with LP over a 10-year period, comparing the proportion of ethnicity in this group with the background ethnicity using UK census data from 2001. Of 26 children included in the study, 21 (80.8%) were from the Indian subcont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 10 publications
3
30
4
5
Order By: Relevance
“…The scarcity of reports may further be due to overall rarity of LP in children, 2-3% of total LP occurring in children below 20 years of age. Under-reporting may also influence the apparent rarity of childhood LP [3].…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity of reports may further be due to overall rarity of LP in children, 2-3% of total LP occurring in children below 20 years of age. Under-reporting may also influence the apparent rarity of childhood LP [3].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In a study from UK also it was found that children originating from the Indian subcontinent represented 80.8% of children with lichen planus suggesting that children from South Asian origin are more susceptible to developing LP. 7 This could be attributed to the difference in the genetic background and environmental triggers or underreporting in other areas. The rarity of associated autoimmune conditions, exposure to drugs and dental restorative materials, infective agents and other environmental triggers that have been known to initiate lichen planus and the overall rarity of LP in children may be responsible for the overall rarity of LP in children.…”
Section: Epidemiologymentioning
confidence: 99%
“…Autoimmune diseases such as chronic active hepatitis, primary biliary cirrhosis, autoimmune thyroiditis, myasthenia gravis, alopecia areata, thymoma, celiac disease, atopic dermatitis and autoimmune polyendocrinopathy have been reported to coexist with lichen planus. 7,9,10 …”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations